From landfill gas to energy : technologies and challenges - Rajaram, Vasudevan; Siddiqui, Faisal Zia.; Emran Khan, M. (Leiden, The Netherlands : CRC Press, 2012)
"A comprehensive description of technologies available for converting old landfills to energy producers, and capturing the green house gases emitting from them. Its key assets are the case studies of successful landfill gas (LFG) recovery for energy projects around the world, and that it highlights why this has not been done in many more landfills around the world. Technical, financial, and social challenges facing the conversion of landfills to energy producers will be detailed, and solutions offered to either remine the landfill for recovering useful land (as is planned in dense urban areas of India) or close them properly while recovering the methane for energy use. Intended as a guide with background information and instructive tools to educate, guide and establish a basis for decision-making, technical feasibility assessment, economic assessment, and market evaluation of all aspects necessary for developing successful LFG management projects. "--
"A Balkema book."
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Gas as fuel; Landfill gases -- Recycling; Gas extraction; Electronic books